The Effectiveness of “Ibu Pintar” Bookmic on Maternal Knowledge and Attitude toward Complementary Feeding Practice in Children Aged 6-24 Months - Lucita, Fifty K.; Yuniastuti, Ari; Farida, Eko (Journal of Maternal and Child Health, 2022)
Background: Complementary Feeding Practice is an important factor for the fulfilment of children’s nutritional needs. Due to the nutritional imbalance between the energy and nutrient needed by infants and what provided by breastmilk, therefore it should be fulfilled by comple- mentary feeding. One third of toddlers worldwide are in developing countries who obtain adequate complementary feeding, with a standard frequency and variety. Meanwhile, in Indonesia two third or most of the children aged 0-24 months do not obtain appropriate complementary food. The study aims to develop “Ibu Pintar” Bookmic, a media which is valid and effective to improve maternal knowledge and attitude in appropriate complementary feeding practice. Subjects and Method: The design of the study used 2 methods. The first method was Research and Development to collect user data and subsequently generated a product that can be utilized to improve knowledge and attitude of mothers of toddlers. The second method was quasi expe- rimental design conducted before and after the study without any comparison to apply Paired Sample T-Test by using SPSS. Results: The result indicated that after the treatment with “Ibu Pintar” Bookmic maternal knowledge in complementary feeding practice was improved (Mean= 1.42; SD= 0.67) compared to maternal knowledge in complementary feeding practice before the treatment (Mean= 0.66; SD; 0.77), and the result was statistically significant (p < 0.001). After the treatment with “Ibu Pintar” Bookmic maternal attitude in complementary feeding practice was improved (Mean= 0.76; SD= 0.43) compared to maternal attitude in complementary feeding practice before the treatment (Mean= 0.44; SD; 0.50), and the resulf was statistically significant (p < 0.001). Conclusion: “Ibu Pintar” Bookmic is effective for maternal knowledge and attitude in complementary feeding practice. Keywords: knowledge, attitude, and complementary food. Correspondence: Fifty K. Lucita. Master’s Program in Public Health, Universitas Negeri Semarang. Email: fifty.kaa@gmail.com. Mobile: +62 858-6922-1419.